Supply Chains : a Manager's Guide - Taylor, Ph. D. (Addison-Wesley Professional, 2003)
"An excellent summary of the state of supply chain management going into the twenty-first century. Explains the essential concepts clearly and offers practical, down-to-earth advice for making supply chains more efficient and adaptive. Truly a survival guide for executives as they struggle to cope with the increasing competition between supply chains."--Christian Knoll, Vice President of Global Supply Chain Management, SAP AG "Through real-world case studies and graphic illustrations, David Taylor clearly demonstrates the bottom-line benefits of managing the supply chain effectively. Although the book is written for managers, I recommend it for everyone from the executive suite to the shipping floor because they all have to work together to master the supply chain. But beware-you can expect many passionate employees demanding improvements in your company's supply chain after reading this book!" - David Myers, President, WinfoSoft Inc., Former Board Member of Supply Chain Council "A comprehensive, thoroughly researched, and well-designed book that gives managers the information they need in a highly readable form. I am already starting to use the techniques in this book to improve our international distribution system." - Jim Muller, Vice President of Produce Sales, SoFresh Produce "Supply chain management is a deceptively deep subject. Simple business practices combine to form complex systems that seem to defy rational analysis: Companies that form trading partnerships continue to compete despite their best efforts to cooperate; small variations in consumer buying create devastating swings in upstream demand, and so on. In his trademark fashion, Taylor clearly reveals the hidden logic at work in your supply chain and gives you the practical tools you need to make better management decisions. A must-read for every manager who affects a supply chain, and in today's marketplace there are few managers who are exempt from this requirement." - Adrian J. Bowles, Ph. D., President, CoSource.net "David Taylor has done it again. With his new book, David makes supply chain management easy to grasp for the working manager, just as he did with his earlier guides to business technology. If you work for a company that is part of a supply chain, you need this book." - Dirk Riehle, Ph. D. "David Taylor has done a masterful job of defining the core issues in supply chain management without getting trapped in the quicksand of jargon. This concise book is wel ...